History of the Sitompul Clan in Huraba Village, South Tapanuli Regency (1803-2023) - Sitompul, Nur Sonia; Rohani, Laila (Yupa: Historical Studies Journal, 2024)
The Sitompul clan is one of the Toba Batak clans that originally settled in Tarutung, North Tapanuli. As a result of the Padri War (1803-1838), a conflict between the Padri and the Minangkabau indigenous people which then spread to the Batak region, the Sitompul clan migrated to various places, including to Huraba Village, South Tapanuli Regency. This research aims to analyze the migration process of Sitompul Clan to Huraba Village and the Islamization process in Huraba Village. This research uses the historical method with four stages: heuristics, source criticism, interpretation, and historiography. Data collection was conducted through document study, field observation, and in-depth interviews. The results show that the migration of the Sitompul clan to Huraba village occurred in several waves, starting in the early 19th century as a direct result of the Padri War. The process of Islamization in Huraba Village took place gradually, starting with the entry of Muslim traders and continued with the spread of Islamic teachings by local religious figures. This Islamization brought significant changes in the social and cultural structure of the Sitompul clan community in Huraba village. This article contributes to a deeper understanding of the dynamics of migration and cultural transformation in the context of local history, as well as enriching insights into the local wisdom of the Batak people.